2011
DOI: 10.2147/ijn.s17057
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun chitosan-graft-poly (ε-caprolactone)/poly (ε-caprolactone) nanofibrous scaffolds for retinal tissue engineering

Abstract: A promising therapy for retinal diseases is to employ biodegradable scaffolds to deliver retinal progenitor cells (RPCs) for repairing damaged or diseased retinal tissue. In the present study, cationic chitosan-graft-poly(ɛ-caprolactone)/polycaprolactone (CS-PCL/PCL) hybrid scaffolds were successfully prepared by electrospinning. Characterization of the obtained nanofibrous scaffolds indicated that zeta-potential, fiber diameter, and the content of amino groups on their surface were closely correlated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…As the solution is ejected from the needle, the solvent evaporates forming individual continuous fibers deposited on the collecting plate. Fibrous electrospun scaffolds produced from PCL and the biomaterial chitosan, which has been covalently bonded to PCL, as well as blends of the two materials, were compared for their engineered properties and their cellular effects [39]. The scaffolds produced from the different materials formed similar scaffolds with fiber mats containing a random orientation with a mean diameter between 656 and 925 nm and containing a porosity between 77 and 89%, with smaller fiber diameter scaffolds being less porous.…”
Section: Fibrous Scaffoldsmentioning
confidence: 99%
“…As the solution is ejected from the needle, the solvent evaporates forming individual continuous fibers deposited on the collecting plate. Fibrous electrospun scaffolds produced from PCL and the biomaterial chitosan, which has been covalently bonded to PCL, as well as blends of the two materials, were compared for their engineered properties and their cellular effects [39]. The scaffolds produced from the different materials formed similar scaffolds with fiber mats containing a random orientation with a mean diameter between 656 and 925 nm and containing a porosity between 77 and 89%, with smaller fiber diameter scaffolds being less porous.…”
Section: Fibrous Scaffoldsmentioning
confidence: 99%
“…Also, in the center, zero CNO À ions are detected, whereas in the same area, the presence of C 6 H 11 O 3 À ions is evident, which shows that chitosan deposition failed in this specific position. Previously, negative zeta potentials for PCL nanofiber scaffolds have been measured which clearly demonstrates that the negative carbonyl oxygen is present at the surface [36,37]. Clearly, the dip coating strategy carried out in this work fails to deposit a controlled homogeneous chitosan coating on both 2D solid discs of pure PCL.…”
Section: Xps and Tof-sims Analysismentioning
confidence: 72%
“…Our previous research has clearly demonstrated that the arrangement of fibers facilitates the invasion of host endothelial cells, thus promoting angiogenic activity, especially in the intraperitoneal environment [29]. …”
Section: Discussionmentioning
confidence: 99%